Height After Side: Goalkeepers Detect the Vertical Direction of Association-Football Penalty Kicks From the Ball Trajectory - Higueras-Herbada, Alfredo; Lopes, José E.; Travieso, David; Ibáñez-Gijón, Jorge; Araújo, Duarte; Jacobs, David M. (Frontiers in Psychology, 2020)
The present research analyzes the relation between the height of penalty kicks in association football and (a) the probability that goalkeepers stop the ball, (b) the kinematics of the kicker, and (c) the movements of the goalkeeper. We re-analyzed movement registration data that were collected in an experiment (with professional and semi-professional players) that focused on the horizontal direction of the penalties (Lopes et al., 2014). We also digitized and analyzed regular videos of the goalkeepers that were recorded by Lopes et al. but not analyzed. The present research complements the current understanding of the penalty kick with three main observations. First, goalkeepers save penalties at middle heights more often than low and high penalties. Second, the height of penalties is predicted less clearly than their horizontal direction from the kinematics of penalty takers. Third, goalkeepers tend to initiate the horizontal component of the saving action before the moment of ball contact, but they initiate the vertical component of the action about 245 ms after the penalty taker contacts the ball. Taken together, these results support the view that goalkeepers make the left-right decision at least partly focusing on the kinematics of the kicker, and that they dynamically decide the vertical aspects of the movement later, focusing on the ball trajectory.